Uteropexy in Sheep as Potential Method for Prevention of Uterine Torsion - Spasojevic, Jovan; Sekulic, Slobodan; Toholj, Bojan; Jakovljevic, Branislava; Stancic, Ivan; Pihler, Ivan; Galic, Ivan (Acta Scientiae Veterinariae, 2022)
Background: Uterine torsion is one of many causes of dystocia in sheep. Failure in performing of wright-time diagnostic procedures and treatment by certain obstetric procedures, can result with death of both fetus and ewe. There is sufficient knowledge about risk factors which could contribute to the occurrence of uterine torsion in sheep, but there is insufficient knowledge about measures for prevention of uterine torsion. The aim of this study was to evaluate the effects of performing incorporative uteropexy as potential method for prevention of uterine torsion. Cases: This research was part of the experimental research of changes in the anterior presentation in sheep fetuses due to their ventro-sacral position in the 2nd half of gestation. At the same sheep farm where afore mentioned research was conducted, the farmer has reported the death of 3 pregnant ewes. In all of 3 animals, torsion of the uterus was diagnosed by patho-anatomical examination. This study was conducted on 6 ewes. All of the animals were in the period around the 100th day of pregnancy at the time of clinical examination. The exact day of pregnancy was not determinated because of free mating in the herd. Confirmation of pregnancy in all of 6 ewes was performed by ultrasound examination. Uniparous pregnancy was found in all of 6 ewes. The entire surgical procedures were performed in the field conditions. Laparotomy was performed in the animals positioned in the left lateral recumbency. Surgical procedure of incorporative uteropexy was performed during the closure of muscle layers of abdominal wall. In need for experimental research of changes in the anterior presentation in sheep fetuses due to their ventro-sacral position in the second half of gestation, 14 days after surgical procedures were conducted, all of sheep were positioned by assistants into a sitting position so that their trunks were vertical to the ground and kept in that position for 2 min. Ultrasound examination of surgical place of uteropexy confirmed that, in all of animals, uteruses were in place of surgical procedures. All of 6 ewes included in this study lambed naturally. One of 6 sheep was sent for economic exploitation on the 14th day after lambing. At the slaughter line, the abdominal wall was evaluated at the site where the incorporative uteropexy was performed. Patho-anatomical examination revealed tissue adhesions at the junction of the uterine horn with the abdominal wall. Discussion: Postsurgical tissue adhesions develop during normal healing process of tissue. According to our knowledge, previous studies do not mention effective measures that could contribute to the prevention of uterine torsion in sheep, but attention is focused on prompt diagnosis and treatment of the disease. According to the results of this study, postsurgical tissue adhesions were developed and confirmed by patho-anatomical examination in 1 sheep. Other 5 sheep were not economically exploited or sacrificed, and no studies were performed to establish the presence of postsurgical tissue adhesions. In conclusion, it could be said that incorporative uteropexy could be considered as preventive procedure in order to avoid the development of uterine torsion in ewes which have shown a history of this pathology, but also in ewes with identified risk factors for the disease. In future studies, it is necessary to identify more parameters which will contribute to identification of sheep which have high risk factors to obtain the torsion of uterus. Also, it is necessary to use non-invasive methods of clinical diagnostics, primary ultrasound diagnostic, to evaluate the area of ​​incorporative uteropexy in order to assess newly formed tissue adhesions as well as to assess the vitality of fetus. It is necessary to follow the lambing process of ewes with incorporated uterus, and to provide medical assistance to the animals if complications occur during the lambing time. Keywords: sheep, uterus, fetus, torsion, incorporative uteropexy.